Bonjour, pouvez vous m'aider à completer ceci ?

fx --> -3X + 2

g: x --> -2/3 x + 1

h: x --> 3.2x - 5

f (3)=

f ( . . . . )2

f (−2) = . . . .

f ( . . . . ) = −9

f (−5/3 ) = . . . .

f ( . . . . ) = 13/5

g (3) = . . . .

g ( . . . . ) = 7

g (−2)= . . . .

g ( . . . . ) = 1/3

g ( 3/4 ) = . . . .

g ( . . . . ) = 5/6

merci à tous !!!

2

Réponses

  • Utilisateur Brainly
2013-06-23T13:42:55+02:00

fx --> -3X + 2

g: x --> -2/3 x + 1

h: x --> 3.2x - 5

 

f (3)=-7

f ( 0)=2

f (−2) = 8

f ( 11/3 ) = −9

f (−5/3 ) = 7

f ( -1/5 ) = 13/5

g (3) = -1

g ( 9 ) = 7

g (−2)= 7/3

g ( 1 ) = 1/3

g ( 3/4 ) =1/2

g ( 1/4 ) = 5/6

2013-06-23T15:12:50+02:00

f : x → -3x + 2

g : x → -2/3 x + 1

h : x → 3.2 x - 5

 

f(3) = -7                          car    f(3) = -3(3) + 2 = -9 + 2 = -7 

 

f(0) = 2                           car    -3x + 2 = 2   ⇔   -3x = 2 - 2   ⇔   x = 0

 

f(-2) = 8                          car    f(-2) = -3(-2) + 2 = 6 + 2 = 8

 

f(11/3) = -9                     car   -3x + 2 = -9    ⇔   -3x = -9 - 2   ⇔   x = -11/-3 = 11/3

 

f(-5/3 ) = 7                      car   f(-5/3) = -3(-5/3) + 2 = 5 + 2 = 7

 

f(-1/5) = 13/5                  car   -3x + 2 = 13/5   ⇔   -3x = 13/5 - 10/5   ⇔   x = 3/5 × 1/-3 = -1/5

 

g(3) = -1                        car   -2/3 (3) + 1 = -2 + 1 = -1

 

g(-9) = 7                        car   -2/3 x + 1 = 7   ⇔   -2/3 x = 7 - 1   ⇔   x = 6 × -3/2 = -9

 

g(-2) = 7/3                     car   -2/3 (-2) + 1 = 4/3 + 1 = 7/3

 

g(1) = 1/3                      car   -2/3 x + 1 = 1/3   ⇔   -2/3 x = 1/3 - 3/3 = -2/3   ⇔   x = 1

 

g(3/4) = 1/2                   car   -2/3 (3/4) + 1 = -6/12 + 1 = 1/2

 

g(1/4) = 5/6                   car   -2/3 x + 1 = 5/6   ⇔  -2/3 x = -1/6   ⇔   x= -1/6 × -3/2 = 1/4